Corporate Sovereign Awakening and the Making of Modern State Sovereignty: New Archival Evidence from the English East India Company - Srivastava, Swati (International organization, 2022)
The English East India Company's “company-state” lasted 274 years—longer than most states. This research note uses new archival evidence to study the Company as a catalyst in the development of modern state sovereignty. Drawing on the records of 16,740 managerial and shareholder meetings between 1678 and 1795, I find that as the Company grew through wars, its claim to sovereign authority shifted from a privilege delegated by Crown and Parliament to a self-possessed right. This “sovereign awakening” sparked a reckoning within the English state, which had thus far tolerated ambiguity in Company sovereignty based on the early modern shared international understanding of divisible, nonhierarchical layered sovereignty. But self-possessed nonstate sovereignty claimed from the core of the state became too much. State actors responded by anchoring sovereign authority along more hierarchical, indivisible foundations espoused by theorists centuries earlier. The new research makes two contributions. First, it introduces the conceptual dynamic of “war awakens sovereigns” (beyond making states) by entangling entities in peacemaking to defend sovereign claims. Second, it extends arguments about the European switch from layered sovereignty to hierarchical statist forms by situating the Company's sovereign evolution in this transformation. Ultimately, this study enables fuller historicization of both nonstate authority and the social construction of sovereignty in international politics.